2012
DOI: 10.1002/ptr.4696
|View full text |Cite
|
Sign up to set email alerts
|

Improving BPH symptoms and sexual dysfunctions with a saw palmetto preparation? Results from a pilot trial

Abstract: In elderly men, benign prostatic hyperplasia (BPH) is a major risk factor for sexual dysfunctions (SDys). Additionally, the standard treatments for BPH symptoms, alpha blockers and 5-alpha-reductase inhibitors, cause SDys themselves. Preparations from saw palmetto berries are an efficacious and well-tolerated symptomatic treatment for mild to moderate BPH and have traditionally been used to treat SDys. We conducted an open multicentric clinical pilot trial to investigate whether the saw palmetto berry preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Although the European Association of Urology is unable to make specific recommendations about plant extracts treatment in patients with LUTS/BPH because of the heterogeneity of the marketed products and the methodological problems associated with meta-analysis, their use in clinical practice is rising with an increased global prescription index, particularly in some European countries (Belgium, Hungary, Poland, France) [2,4,5]. Furthermore, the treatment of BPH with α-blockers and 5α-reductase inhibitors could play an important role in the alteration of sexual functions leading to ejaculatory and erectile disorders [6]. To avoid this issue, natural products derived from plants have been using for treating BPH, especially extracts of Serenoa repens (saw palmetto) obtained from the American dwarf palm [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…Although the European Association of Urology is unable to make specific recommendations about plant extracts treatment in patients with LUTS/BPH because of the heterogeneity of the marketed products and the methodological problems associated with meta-analysis, their use in clinical practice is rising with an increased global prescription index, particularly in some European countries (Belgium, Hungary, Poland, France) [2,4,5]. Furthermore, the treatment of BPH with α-blockers and 5α-reductase inhibitors could play an important role in the alteration of sexual functions leading to ejaculatory and erectile disorders [6]. To avoid this issue, natural products derived from plants have been using for treating BPH, especially extracts of Serenoa repens (saw palmetto) obtained from the American dwarf palm [7-9].…”
Section: Introductionmentioning
confidence: 99%
“…SP have a long standing use in the treatment of mild to moderate LUTS and ED 3, 4, 5, 6, 7. More than 30 controlled clinical trials evaluating treatments for LUTS and SDys have demonstrated long-term efficacy 5, 6, 7.…”
Section: Discussionmentioning
confidence: 99%
“…SP have a long standing use in the treatment of mild to moderate LUTS and ED 3, 4, 5, 6, 7. More than 30 controlled clinical trials evaluating treatments for LUTS and SDys have demonstrated long-term efficacy 5, 6, 7. The plant, which is indigenous to Florida, was first used by white settlers in the United States not only for treatment of LUTS but also a treatment for ED, to improve testicular atrophy and sperm production 3, 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations